MODEL TO DETERMINE THE PERCEIVED RISKS OF TOURISTS STAYING AT HOTELS WHERE THE HALAL TOURISM CONCEPT IS PRESENT: ANTALYA REGION EXAMPLE - Yenal Yagmur; Akin Aksu (Enlightening Tourism: A Pathmaking Journal)
The aim of this study was to determine the risk perception of tourists in relation to the concept of halal tourism, and to reveal the relationships between risk perception, satisfaction and behavioral intention. The study used a quantitative research design based on the application of a questionnaire. Simple random sampling was used as the sampling method. The questionnaire developed by Olya and Al-ansi (2018) was employed in this research, and the proposed model was analyzed through the structural equation modelling (SEM) technique. It was found that the health risk dimension had a positive impact on tourist satisfaction while the social and time risk dimensions affected tourist satisfaction negatively and significantly. In addition, it was concluded that none of the seven risk dimensions (health, psychological, environmental, social, quality, financial and time) significantly affected the tourists’ intention to recommend whereas the health and financial risk dimensions affected the tourists’ continued intention to use halal items negatively and significantly.